Cultural Tourism: A Review of Karnali (Research Nepal Journal of Development Studies, 2021)
“Cultural Tourism: A review of Karnali” is the collection of facts of interesting cultural tourism attractions of Karnali province of Nepal. If there is heaven, it exists in Karnali. Its natural and cultural attractions accommodate a wonderland to visit. The paper is focused on the cultural attractions of Karnali Province. To generalize the facts of culture of Karnali from tourism perspective the study has been conducted. It is the scientific but descriptive literature review of available sources. The paper will be a perfect guideline for field researchers of cultural tourism in Karnali. In conclusion, Nepal is one of the pristine center of natural and cultural tourism attraction. Nepal’s most beautiful natural and cultural attraction is Karnali. There are around 30% of Khasaryan population in Nepal, literally originated from Khasasn kingdom. Karnali stakeholders must analyze the sentiment of Khasaryan of their ancestral kingdom with different programs and invitations. Karnali tourism is a set of distinctive material, intellectual, spiritual and emotional features of the society. It encompasses arts and architecture, historical and cultural heritage, literature, music, and the living cultures with their lifestyles, value systems, beliefs and traditions of Karnali. Specifically culture of Khasaryan, Mashto worship, Deuda, Himalayan Buddhism, Rara and pilgrimage to Kailash Mansarovar are the prominent cultural attractions of Karnali.